Self-efficacy, drug side effects, and nurse communication: Factors related in chemotherapy adherence for breast cancer patients - Muhammad Ashraf; Hema Malini; Randy Refnandez; Intan Yullya Kardila (Faculty of Nursing Universitas Padjadjaran, 2025)
Background: Chemotherapy is a crucial therapy for breast cancer patients, and its success heavily depends on patient compliance. However, despite extensive in the impact of Non-compliance, there is still limited understanding of the specific factors influencing chemotherapy adherence among breast cancer patients, highlighting the need to re identify these contributing factors. Purpose: This study aims to identify the determinant factors related to chemotherapy adherence among breast cancer patients at the West Sumatera Provincial Hospital. Methods: This study is a quantitative research with a cross-sectional design. An accidental sampling technique was used, with a total of 81 patients. Bivariate analysis was conducted using the chi-square test (p < 0.05), and multivariate analysis was performed using Multiple Logistic Regression. Results: The results showed that 61.7% of patients had good compliance. Factors associated with compliance included good self-efficacy, low knowledge, feeling bothered by the side effects of chemotherapy drugs, and effective nurse interpersonal communication. Multivariate analysis revealed that self-efficacy and drug side effects had a significant relationship with compliance (p < 0.05). Drug side effects were the most significant factor (OR = 12.223, 95% CI: 1.371 to 109.015, p < 0.05). Conclusion: The findings of this study highlight the importance of managing drug side effects and enhancing self-efficacy through patient education and improved nurse interpersonal communication. These measures are expected to improve the quality of nursing care and patient outcomes.